The impact of transition interventions for young people leaving care: a review of the Australian evidence. Issue 1 (31st December 2020) - O'Donnell, Renée; Hatzikiriakidis, Kostas; Mendes, Philip; Savaglio, Melissa; Green, Rachael; Kerridge, Gary; Currie, Graeme; Skouteris, Helen
ABSTRACT: Whilst advancing outcomes for young people transitioning from out-of-home care is a national priority, no synthesis of Australian interventions that support their transition from care and into independence currently exists. The aim of this systematic scoping review was to examine the characteristics of such interventions delivered in Australia and to evaluate their impact. Papers were included if they assessed the extent to which transitional support interventions, delivered in Australia, improved housing, employment, education, financial, health, or social functioning outcomes. Eleven studies were included. Interventions primarily adopted a case management approach to support care-leavers' transition. Interventions facilitated improvements in care-leavers' independent living outcomes (e.g., housing, education, and financial stability), but less so in health outcomes. This synthesis provides guidance for how research organizations in partnership with community service organizations and statutory services should develop and deliver interventions to support young Australians transitioning from care.